2007
DOI: 10.1161/01.str.0000247920.15708.fa
|View full text |Cite
|
Sign up to set email alerts
|

Induced Hypothermia for Acute Stroke

Abstract: Abstract-Induced

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(61 citation statements)
references
References 76 publications
1
58
0
2
Order By: Relevance
“…Therapeutic hypothermia-Moderate therapeutic hypothermia represents one of the most solidly evidence-based neuroprotective strategies currently available (Hemmen et al, 2007). A large corpus of experimental studies over the past 20 years has provided incontrovertible evidence that moderate hypothermia is capable of conferring high-grade neuroprotection in focal and global cerebral ischemia by impeding a host of deleterious metabolic and biochemical injury-mechanisms, with a therapeutic window appropriate for clinical application in ischemic stroke (Ginsberg et Group, 2002).…”
Section: Part Ii: Neuroprotection --Moving From the Present Into The mentioning
confidence: 99%
“…Therapeutic hypothermia-Moderate therapeutic hypothermia represents one of the most solidly evidence-based neuroprotective strategies currently available (Hemmen et al, 2007). A large corpus of experimental studies over the past 20 years has provided incontrovertible evidence that moderate hypothermia is capable of conferring high-grade neuroprotection in focal and global cerebral ischemia by impeding a host of deleterious metabolic and biochemical injury-mechanisms, with a therapeutic window appropriate for clinical application in ischemic stroke (Ginsberg et Group, 2002).…”
Section: Part Ii: Neuroprotection --Moving From the Present Into The mentioning
confidence: 99%
“…At the clinical level, however, the role of therapeutic hypothermia in the treatment of stroke remains unclear, due to certain problems in translating preclinical data to the clinical arena. 3,5,10,14) For instance, it is difficult to prevent shivering and other discomforts experienced because most stroke patients are awake and not endotracheally intubated. Hypothermia is most effective in preclinical models of transient ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…However, many serine proteases are affected by temperature, and the activity of tPA may be reduced in hypothermia. [54] In vitro analysis shows that cooling to 30°C to 33°C decreases tPA activity by 2% to 4%. [55] Moreover, it has been reported that the response to tPA may be related to body temperature at stroke presentation.…”
Section: Hypothermia and Thrombolysismentioning
confidence: 99%
“…[47] In the ICTuS-L trial, the rate of ICH was similar among patients who received tPA with hypothermia and those treated with tPA alone. [51] Hypothermia has also been studied with other neuroprotective agents in the treatment of acute ischemic stroke. Twenty patients with acute ischemic stroke were treated with caffeinol (caffeine 8-9 mg/kg + ethanol 0.4 g/kg intravenously x 2 hours, started by 4 hours after symptom onset) and hypothermia (started by 5 hours and continued for 24 hours (33-35º C), followed by 12 hours of rewarming).…”
Section: Human Studies Of Hypothermia In Ischemic Strokementioning
confidence: 99%